Genital herpes in women during and outside of pregnancy - S. V. Pavlovich; N. M. Nazarova (Медицинский совет, 2018)
Annually, about 500 thousand people get new genital herpes (GH) infections. The incidence of GH in Russia was 13.5 cases per 100 thousand people in 2015. According to the WHO (2015), 67% of population is infected with herpes simplex virus. The numerous studies in general population showed that women were infected more often than men with the same number of sexual partners during life, and the highest incidence of GH was recorded in the age group between 20 and 29 years, and the second peak incidence was recorded at the age of 35–40 years [1–3].